Political official turnover and environmental governance: who is more influential on local air pollution in China - Chun Yang; Jun Zhang; Ruilin Li (Humanities & Social Sciences Communications)
Abstract Political factors are widely acknowledged determinants of local environmental outcomes, yet their precise influence on air pollution, particularly in the context of leadership transitions, remains a subject of ongoing debate without a clear consensus. This study addresses this gap by investigating the impact of changes within China’s dual local political system—the government and Party systems—on air quality in prefectural-level cities. Leveraging mayoral turnover and Party secretary turnover as indicators of these system changes, we analyze their impact on local air pollution levels. Utilizing a difference-in-difference model, we estimate the effects using monthly data on local political official turnover and air quality collected from 337 Chinese cities over a 36-month period. Our findings reveal significant and differentiated short-term impacts of mayoral and Party secretary turnover on local air pollution. Specifically, we observe a deterioration in air quality in the months following mayoral turnover, while Party secretary turnover shows no significant immediate impact. Furthermore, the effect of mayoral turnover is heterogeneous, varying significantly with regional characteristics, the geographic origin and age of the newly appointed official, the former official’s tenure, and the central government's environmental inspections. This research contributes to understanding the distinct roles of different local political leadership in shaping environmental governance outcomes in China.